Relationship of Body Mass Index and Waist Hip Ratio with Insulin Resistance in Polycystic Ovarian Syndrome Patients - Hoque, Asma; Aziz, Rehana; Karmakar, Pijush; Hossain, Nadia; Hussain, Farhad; Uddin, Rafiq (IAHS Medical Journal, 2022)
Background: Polycystic Ovarian Syndrome (PCOS) is the most common endocrinopathy among young women. Insulin resistance is a key feature in the pathogenesis of PCOS. Obesity, which is frequently associated with PCOS women, seems to amplify the degree of insulin resistance. The aim of the study is to investigate the relationship of insulin resistance with obesity in PCOS patients. Materials and methods: This was a hospital based cross-sectional study comprising fifty (50) diagnosed PCOS patients aged between 20 and 40 years. This study was carried out in the Department of Biochemistry, Chittagong Medical College (CMC) and inpatients, outpatient Department of Gynaecology and Obstetrics, Chittagong Medical College Hospital (CMCH). Samples were taken by non-probability purposive sampling. Results: The percentage of Insulin Resistance (IR) was 60% in this study. Mean age of PCOS patients was 30.6±0.65years. Obese PCOS patients with insulin resistance were 46% and overweight PCOS patients with IR were 48% in this study. There were also significant positive association of IR with increased BMI and waist hip ratio. Additionally 06% non-obese PCOS patients showed IR in this study cases. Conclusions: This study suggested that abdominal obesity was a good predictor of IR among PCOS patients. So, waist circumference or waist hip ratio may be used as a screening tool for IR risk assessment among PCOS patients as an inexpensive, noninvasive and easy-to-detect marker. Hence early diagnosis and proper preventive management of these patients will reduce the reproductive complications. IAHS Medical Journal Vol 4(2), December 2021; 3-7